Students' Creativity Profile Using Project Report through the STEM integrated Project Based Learning Model - Hendriyani, Mila Ermila; Rifqiawati, Ika; Usman, Usman (Jurnal Pendidikan Indonesia Gemilang, 2023)
Creativity is related to mental activities to build new ideas. Students' creative thinking skills need to be developed to overcome problems in everyday life, such as discovering and creating new things, new ways, and new models that are useful for themselves and others. Creative thinking is also a skill that demands 21st-century competencies developed through applying the curriculum 2013. The Project Based Learning (PjBL) is a recommended learning model in the curriculum 2013. The purpose of this study is to measure student creativity in compiling project reports. These creative thinking skills are developed through the Human Physiology Anatomy Course (Anfisman) by applying project-based STEM-integrated PjBL. The project in question is to explore problems in the form of diseases or abnormalities in the body system often suffered by the community and their solutions. Then the project report is packaged in the form of a video. The method used in the study is the mixed method with an explanatory design. The research sample was Anfisman class students, who were selected by purposive sampling totaling 38 people. The instruments used are creative product assessment and STEM-integrated PjBL implementation sheets. The results showed that students have good creative thinking skills, shown by the results of their project report products in the form of videos. Project reports in the very creative category, as much as 12%. In the creative category, as much as 75%, and in the quite creative category, as much as 13%. It also shows that the STEM-integrated PjBL model can grow and develop students' creative thinking skills.